2011
DOI: 10.1111/j.1399-0012.2011.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Portrayal of organ donation and transplantation on American primetime television

Abstract: Recently, both living and deceased organ donation rates have hit a plateau, despite increases in need for viable organs. One approach to improve donation rate is public education and policy; thus, it is necessary to understand the information the public is receiving regarding organ donation. We hypothesized that primetime medical dramas portray organ donation and transplantation in a negative manner. We compiled data on all primetime medical drama episodes with transplant themes from November 2008 through June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(21 reference statements)
0
8
0
2
Order By: Relevance
“…8,16,18,19,[23][24][25] In the present study, > 60% medical students indicated that media affected their willingness to donate stem cells (Table 4). To date, media such as television, radio, and newspapers have been the primary sources of information about organ donation and transplantation 14 Media reports may positively affect public attitudes about HSCT and donation in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,16,18,19,[23][24][25] In the present study, > 60% medical students indicated that media affected their willingness to donate stem cells (Table 4). To date, media such as television, radio, and newspapers have been the primary sources of information about organ donation and transplantation 14 Media reports may positively affect public attitudes about HSCT and donation in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies have been undertaken to expand donor pools in many countries, particularly for solid-organ transplantations. [12][13][14][15] Good knowledge of HSCT and stem cell donation in health care professionals can increase the numbers of unrelated donors. 11 Numerous studies that have evaluated knowledge and attitudes among students in Turkey about organ and blood donation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because television is a key source of medical information for the public, the donation community began working with the entertainment industry in 2007 to improve the quality of education about organ donation on medical shows through a project called Donate Life Hollywood. Nonetheless, in a review of 49 episodes of medical dramas from 2008 to 2010 that dealt with organ donation, Harbaugh et al found that negative messages were more prominent than positive messages about donation and transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…As our findings show, unfortunately the entertainment industry does not routinely go to such lengths when portraying brain death. As such, it is very important for physicians, nurses, and organ procurement representatives to partner with television and film writers and producers to ensure accurate portrayals of brain death and organ donation and thereby improve public education on these topics . This may be challenging, as Hollywood may not be open to such efforts.…”
Section: Discussionmentioning
confidence: 99%